An H4K16 histone acetyltransferase mediates decondensation of the X chromosome in C. elegans males. Issue 1 (December 2016) - Lau, Alyssa; Zhu, Kevin; Brouhard, Elizabeth; Davis, Michael; Csankovszki, Györgyi
Abstract Background InC. elegans, in order to equalize gene expression between the sexes and balance X and autosomal expression, two steps are believed to be required. First, an unknown mechanism is hypothesized to upregulate the X chromosome in both sexes. This mechanism balances the X to autosomal expression in males, but creates X overexpression in hermaphrodites. Therefore, to restore the balance, hermaphrodites downregulate gene expression twofold on both X chromosomes. While many studies have focused on X chromosome downregulation, the mechanism of X upregulation is not known. Results To gain more insight into X upregulation, we studied the effects of chromatin condensation and histone acetylation on gene expression levels in maleC. elegans . We have found that the H4K16 histone acetyltransferase MYS-1/Tip60 mediates dramatic decondensation of the male X chromosome as measured by FISH. However, RNA-seq analysis revealed that MYS-1 contributes only slightly to upregulation of gene expression on the X chromosome. These results suggest that the level of chromosome decondensation does not necessarily correlate with the degree of gene expression change in vivo. Furthermore, the X chromosome is more sensitive to MYS-1-mediated decondensation than the autosomes, despite similar levels of H4K16ac on all chromosomes, as measured by ChIP-seq. H4K16ac levels weakly correlate with gene expression levels on both the X and the autosomes, but highly expressed genes on the X chromosome do not contain exceptionally high levels of H4K16ac. Conclusion These results indicate that H4K16ac and chromosome decondensation influence regulation of the male X chromosome; however, they do not fully account for the high levels of gene expression observed on the X chromosomes.